Nitrification and coupled nitrification-denitrification at shallow depths are responsible for early season N2O emissions under alternate wetting and drying management in an Italian rice paddy system. (May 2018) - Verhoeven, Elizabeth; Decock, Charlotte; Barthel, Matti; Bertora, Chiara; Sacco, Dario; Romani, Marco; Sleutel, Steven; Six, Johan
Abstract: There is increasing pressure to reduce water use in irrigated rice production to save water, reduce methane emissions and reduce grain arsenic uptake arising from anaerobic conditions. However, under such practices emissions of nitrous oxide (N2 O) often increase. Rice systems generally exhibit strong stratification of environmental conditions that drive the balance between N2 O production and consumption, and ultimately the emissions of N2 O. We investigated how the introduction of alternate wetting and drying (AWD) relative to conventional flood (FLD) irrigation modifies the depth distribution of environmental conditions and nutrients (NO3 −, NH4 +, dissolved organic carbon, soil redox (Eh) and water filled pore space, (WFPS)). We then examined how these variables related to N2 O production and consumption via the measurement of δ 15 N-N2 O emitted/poreair, δ 15 N-NO3 −, N2 Oturnover and subsurface N2 O fluxes at five depths (5, 12.5, 25, 50 and 80 cm). These measurements, together with N2 O surface emissions were taken on six days surrounding a broadcast urea fertilizer application and for six days surrounding the onset of final drainage. The highest emissions were observed in the AWD treatment at the onset of measurements. These emissions were driven by high NH4 + availability and could mainly be attributed to nitrification directly or indirectly via coupled nitrification-denitrification in the upper depths. In both irrigation treatments, an increase in NO3 − and dissolved N2 O concentrations and a drop in δ 15 N-NO3 − values indicated rapid and ephemeral nitrification following the fertilization, but without significant effects on N2 O surface emissions. At 50 and 80 cm, δ 15 N-N2 O poreair was enriched relative to upper depths, pointing to N2 O reduction at these depths in both treatments. We conclude that the increased N2 O emissions under AWD compared to FLD management were associated with enhanced nitrification in the upper soil layers during plant establishment and thus related to basal N fertilization and mineralization of native soil N rather than in-season fertilization. Highlights: N2 O emissions were highest in the early growing season and in an AWD treatment. Early season emissions were controlled directly or indirectly by nitrification. Subsurface N2 O production was associated with depleted δ 15 N-N2 O at shallow depths.